2009
DOI: 10.1159/000249149
|View full text |Cite
|
Sign up to set email alerts
|

Functional Subtypes of Renal α<sub>1</sub>-Adrenoceptor in Spontaneously Hypertensive Rats with Streptozotocin-Induced Experimental Diabetic Nephropathy

Abstract: Aim: This study investigated the impact of hypertension combined with diabetic nephropathy on rat renal α1-adrenoceptor subtype composition. Methods: In streptozotocin-induced diabetic spontaneously hypertensive rats (SHR), diabetic nephropathy developed as reflected by increased kidney index, plasma creatinine, albumin excretion, creatinine clearance and fractional excretion of Na+ (all p < 0.05). Renal vasoconstrictions caused by electrical stimulation of renal nerves and intrarenally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
8
7
0
Order By: Relevance
“…In the experimentally induced diabetic rats, a significant reduction in the body weight was observed, whereas, STZ lead to same degree of hyperglycemia in all experimental groups. This finding is consistent with the earlier studies of our laboratory that the weight loss is one of the common happening in STZ induced diabetes in rats (32), (33). In a state of experimental diabetes such as type 1, most of β -cells are destroyed leading to hypoinsulinemia and hyperglycaemia due to the decreased utilization of the glucose by the tissues and will lead to reduction in body weight (34).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the experimentally induced diabetic rats, a significant reduction in the body weight was observed, whereas, STZ lead to same degree of hyperglycemia in all experimental groups. This finding is consistent with the earlier studies of our laboratory that the weight loss is one of the common happening in STZ induced diabetes in rats (32), (33). In a state of experimental diabetes such as type 1, most of β -cells are destroyed leading to hypoinsulinemia and hyperglycaemia due to the decreased utilization of the glucose by the tissues and will lead to reduction in body weight (34).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, with the induction of diabetes, SHR diabetic groups exhibited decreased renal cortical blood perfusion (RCBP) and it is in agreement with our previous lab findings (33), which is due to the increased renovascular response to adrenergic and neural stimuli and activation of intra-renal RAAS (41). The hyperglycemia induced by STZ lead to activation of local ANG II (42), which cause increased renovascular resistance, thus leads to reduced RCBP in diabetic rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 Plasma creatinine 26 and creatinine clearance, a measure of glomerular filtration rate (GFR), 8 are commonly used to evaluate the renal hemodynamic function. Khan et al 27 reported that the SHR-STZ model of genetic hypertension and diabetes is one which develops the typical changes in renal injury early in the course of the disease. Interestingly, we have also demonstrated renal injury in terms of increased plasma creatinine and creatinine clearance in the diabetic SHR group.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological and metabolic indices were kept into consideration to assess the experimental diabetes in SHRs, including body weight, which was signi cantly reduced as one of the pronounced effect of STZ on β -cells (38). Polyuria and polydipsia were also observed as signi cant metabolic perturbations of diabetic SHRs and found to be in accordance with the observations of Khan (39).…”
Section: Discussionmentioning
confidence: 53%